Instagram as a data source for sea turtle surveys in shipwrecks in Brazil. (24th June 2022) - Leitão, A. T. T. S.; Alves, M. D. de O; dos Santos, J. C. P.; Bezerra, B.
Abstract: Shipwrecks have been accidentally and deliberately deployed worldwide, becoming artificial reefs for tourist attractions and habitats for marine species. Recreational divers often visit wrecks and post images on Instagram – a popular social network for image circulation. Here we evaluated if such images could be used as a data source for surveying sea turtles in shipwrecks and assessing diver–sea turtle interactions. We targeted the coast of Pernambuco in Brazil, which has over 100 shipwrecks. We inspected public videos and photos posted on Instagram from October 2010 to April 2020. We used 20 tags in our search, which led to 2353 images (210 videos; 2143 photos). A total of 220 posts depicted sea turtles (189 photos and 31 videos; 41 sea turtles in videos and 199 in photos) and their enhanced quality‐facilitated species identification. We detected Caretta caretta (loggerhead sea turtle), Chelonia mydas (green sea turtle) and Eretmochelys imbricata (hawksbill sea turtle) . Turtles were found in 13 shipwrecks, all with bathymetry up to 30 m. Photos and videos provided the same proportion of images of each turtle species. Nevertheless, from a temporal perspective, this scenario changed. All three species were observed in photo posts in 4 of the 9 full years considered, whereas all three species were only observed in 1 year in the video posts. We registered four types of diver–turtle interactions from videos: 'abrupt approach, chase, touch and pose'. We classified 'abrupt approach, chasing and touching' behaviours as major disturbances as they altered the turtles' behaviours. We classified 'pose' as a minor disturbance as it caused no apparent change in turtle behaviour. Chasing was the most frequently observed interaction. Instagram is a useful complementary tool that can aid in the surveillance of sea turtles in shipwrecks. However, the limitations of this type of data and adequate data filtering criteria must be considered. Abstract : Instagram can be used as a complementary tool that can aid in the surveillance of sea turtles in shipwrecks. However, the limitations of social media data and adequate data filtering criteria must be considered.